2007
DOI: 10.1124/mol.106.033233
|View full text |Cite
|
Sign up to set email alerts
|

Analogs of Methyllycaconitine as Novel Noncompetitive Inhibitors of Nicotinic Receptors: Pharmacological Characterization, Computational Modeling, and Pharmacophore Development

Abstract: As a novel approach to drug discovery involving neuronal nicotinic acetylcholine receptors (nAChRs), our laboratory targeted nonagonist binding sites (i.e., noncompetitive binding sites, negative allosteric binding sites) located on nAChRs. Cultured bovine adrenal cells were used as neuronal models to investigate interactions of 67 analogs of methyllycaconitine (MLA) on native ␣3␤4* nAChRs. The availability of large numbers of structurally related molecules presents a unique opportunity for the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 27 publications
2
24
0
1
Order By: Relevance
“…Table 2 established the feasibility of using this cell line. The relative potencies of nicotine, epibatidine, and one of our own antagonists, COB-2, were identical to values reported in the literature for native bovine adrenal nAChRs (McKay and TrentSanchez, 1990;McKay and Burkman, 1993;Wenger et al, 1997;McKay et al, 2007); native nAChRs showed slightly higher apparent affinities for the agonists. The inhibitory effects of the competitive antagonist tubocurarine and the noncompetitive antagonists mecamylamine and tetracaine were also compared (Table 2); no major differences were seen between native bovine and recombinant rat nAChRs.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Table 2 established the feasibility of using this cell line. The relative potencies of nicotine, epibatidine, and one of our own antagonists, COB-2, were identical to values reported in the literature for native bovine adrenal nAChRs (McKay and TrentSanchez, 1990;McKay and Burkman, 1993;Wenger et al, 1997;McKay et al, 2007); native nAChRs showed slightly higher apparent affinities for the agonists. The inhibitory effects of the competitive antagonist tubocurarine and the noncompetitive antagonists mecamylamine and tetracaine were also compared (Table 2); no major differences were seen between native bovine and recombinant rat nAChRs.…”
Section: Resultssupporting
confidence: 68%
“…Allosteric modulators exist for a variety of receptors (Wess, 2005). Allosteric modulation of nAChRs is considered to be one of the most promising approaches in ligand design for nAChR research and therapeutics (Cassels et al, 2005;Iorga et al, 2006), and the characterization and localization of these sites are beginning to be elucidated (Costa et al, 2003;Iorga et al, 2006;McKay et al, 2007).…”
mentioning
confidence: 99%
“…A concerted hypothesis for the nicotinic control of burst firing [40] posits that nicotine rapidly and preferentially desensitises α4β2 nAChRs on GABAergic interneurons [41], relieving inhibition of midbrain dopamine neurons while maintaining a sustained activation of α7 nAChRs on dopaminergic cell bodies as well as glutamate terminals [30]. β2* nAChRs on dopamine cell bodies provide a coincident depolarisation that enhances excitability, and this is necessary for LTP and /or to drive changes in firing pattern.…”
mentioning
confidence: 99%
“…27-30 All of the simple E ring analogues have been shown to be noncompetitive antagonists to the α3β4* nAChR, with no affinity to the agonist binding sites of either α7, α4β2, or α3β4* nAChRs. 31 We hoped that introducing a more rigid conformation to our previous E-ring analogues might provide a selective and competitive ligand to the α7 nAChR. A simple removal of the A, C, D and F rings of MLA provides a BE ring analog.…”
Section: Introductionmentioning
confidence: 99%